Implementation of an Electromagnetic Induction Coil System Integrated With PLC Using an Adaptive Control Method for Enhanced Energy Efficiency - Gun Gun Maulana; Abdur Rohman Harits Martawireja; Nur Wisma Nugraha (Journal of Applied Engineering and Technological Science (JAETS), 2026)
Electromagnetic induction heating is widely used in manufacturing due to its fast and localized heating capability. However, conventional constant-power and fixed PID control methods often struggle with nonlinear and time-varying thermal dynamics, leading to temperature overshoot, long settling times, and inefficient energy use. These limitations highlight the need for adaptive and energy-efficient control strategies, especially in PLC-based industrial systems. This study proposes a PLC-based adaptive control framework using a self-tuning PID algorithm, where control parameters are automatically adjusted in real time based on temperature error and system response. The method enables continuous adaptation to improve thermal tracking under dynamic conditions. Experimental validation was performed by heating workpieces to 600 °C and evaluating performance using rise time, settling time, overshoot, steady-state error, and energy consumption. Compared to a conventional constant-power method, the proposed approach shows significant improvements in transient and steady-state performance, with reduced rise time, settling time, and overshoot. Additionally, energy consumption decreased from 1.6067 kWh to 1.3265 kWh, representing a 17.44% improvement. The integration of PLC enhances real-time system responsiveness and heat uniformity. Overall, the proposed method effectively bridges the gap between fixed control and adaptive, high-performance thermal regulation for Industry 4.0 applications